Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 4 - Section 4.2 - Solving Systems of Linear Equations by Substitution - Exercise Set: 7

Answer

x = - $\frac{1}{5}$ y = $\frac{43}{5}$

Work Step by Step

y = 2x + 9 y = 7x + 10 Substitute y for 2x + 9 to the second equation. 2x + 9 = 7x + 10 2x + ( -7x ) + 9 = 7x + ( - 7x ) + 10 (add - 7x to both sides) - 5x + 9 = 10 - 5x + 9 + ( - 9 ) = 10 + ( - 9 ) - 5x = 1 x = - $\frac{1}{5}$ Substitute x for - $\frac{1}{5}$ to the first equation. y = 2 ( - $\frac{1}{5}$ ) + 9 y = - $\frac{2}{5}$ + $\frac{45}{5}$ y = $\frac{43}{5}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.